The effects of solutionizing temperatures on microstructures of as-received A357 alloy - Mazlee, Mohd Noor; Shamsul Baharin, Jamaludin; Shaiful Rizam, Shamsuddin; Mohabattul Zaman, SNS Bukhari; Khairel Rafezi, Ahmad; Raudhah, Othman (Universiti malaysia Perlis, 2010)
Organized by School of Materials Engineering & Sustainable Engineering Research Cluster, 1st - 2nd December 2009 at Putra Brasmana Hotel, Kuala Perlis, Perlis.